Lethal and sublethal effects of Thiocyclam hydrogen oxalate and Flubendimide on the population growth parameters and population projection of Tuta absoluta (Lepidoptera: Gelechiidae) - Sara Ebne abbasi; Fariba Mehrkhou; Maryam Forouzan (نامه انجمن حشره‌شناسی ایران, 2000)
The tomato leafminer moth, Tuta absoluta (Meyrick), is a key pest in greenhouses and tomato-growing regions in the world. In the present study, the lethal and sublethal (LC25) effects of two insecticides, thiocyclam hydrogen oxalate, and flubendiamide were evaluated on the life table parameters of T. absoluta under laboratory conditions. The leaf dipping was used for the bioassays. The life table data were analyzed based on the age-stage, two-sex life table theory. The results showed that thiocyclam hydrogen oxalate (LC50: 175.327 ppm) was more toxic than flubendiamide (LC50: 219.759 ppm) on the T. absoluta eggs. However, the sublethal concentrations of mentioned insecticides affected the life table parameters of T.absoluta significantly compared with the control, but flubendiamide prolonged the developmental time (embryonic, pre-adult, and pupal period) of T. absoluta, significantly more than thiocyclam hydrogen oxalate. Also, the population growth parameters such as intrinsic rate of increase, finite rate of increase, and net reproductive rate of insects treated by insecticides were lower than the control, significantly. The total results revealed that either thiocyclam hydrogen oxalate or flubendiamide have admissible lethal and sublethal effects on tomato leafminer eggs and can be considered in the integrated pest management program (IPM) of this pest.